Anisotropic Elastic Properties of Montmorillonite With Different Layer Charge Densities and Layer Charge Distributions Through Molecular Dynamic Simulation - Wang, Xueying; Han, Tongcheng; Fu, Li-Yun (Frontiers in Earth Science, 2022)
The knowledge of the anisotropic elastic properties of clay minerals is of crucial importance for the exploration and development of shale gas. Montmorillonite (MMT) is a common natural clay mineral with different layer charge densities and layer charge distributions due to different geological conditions. Therefore, it is important to understand the currently poorly unknown effect of layer charge density and layer charge distribution on the anisotropic elastic properties of MMTs. This work aims to obtain such knowledge by studying the anisotropic elastic properties of different MMTs under stratigraphic conditions through molecular dynamic simulations. We showed that the in-plane compressional coefficients C11, C22 and C12 decrease with the increasing charge density increases for MMTs with different layer charge distributions, and the MMTs with the layer charges distributed on the two tetrahedral (T) sheets were found to have the smallest C11, C22 and C12. We also showed that the out-of-plane compressional coefficients C33, C13 and C23 of the MMTs with the layer charges distributed in the two T sheets decrease, while those with the layer charges in the octahedral (O) sheet increase and those with layer charges distributed in both the O sheet and the T sheets do not vary much with the increasing layer charge density. The variations of the anisotropic compressional elastic coefficients with different layer charge densities and layer charge distributions were found to be a result of the impact of the density and distribution of layer charges on the molecular interactions within the MMT layer. We further demonstrated that the layer charge density and layer charge distribution do not influence significantly the shear coefficients C44, C55, and C66. The results revealed the mechanisms of how the density and distribution of layer charges affect the anisotropic elastic properties of MMTs and will contribute to the more successful exploration and development of unconventional resources in MMT bearing shale reservoirs.